The effect of target detection task on memory encoding varies in different stimulus onset asynchronies. - Shang, Chenyang; Sun, Meng; Zhang, Qin (Memory & Cognition, 2024)
The attentional boost effect (ABE) and action-induced memory enhancement (AIME) suggest that memory performance for target-paired items is superior to that for distractor-paired items when participants performed a target detection task and a memory encoding task simultaneously. Though the memory enhancement has been well established, the temporal dynamics of how the target detection task influenced memory encoding remains unclear. To investigate this, we manipulated the stimulus onset asynchrony (SOA) between detection stimuli and the words to be memorized using a remember/know study-test paradigm, and we focused primarily on memory performance for the words that appeared after the detection response. The results showed that target-paired memory enhancement was robust from SOA = 0 s to SOA = 0.75 s, but was not significant when examined by itself in Experiment 1A or weakened in Experiment 2 and the conjoint analysis when SOA = 1 s, which were only observed in R responses. The post-response memory enhancement still existed when there was no temporal overlap between the word and target, similar to the magnitude of memory enhancement observed with temporal overlap. These results supported the view that target-paired memory enhancement (recollection rather than familiarity) occurred irrespective of whether the items appeared simultaneously with the targets or within a short period after the response, and the temporal overlap of the word and target was not necessary for post-response memory enhancement.